Consumers of Generations Y and Z and their Expectations from Companies in terms of CSR - Alicja Katarzyna KRZEPICKA (Communications of International Proceedings, 2021)
Activities in the field of social responsibility are for many enterprises operating on the modern market, routine, for some following trends, and for others, the style of doing business assuming that the enterprise does not exist in a vacuum, but in the market environment. Functioning in it has not only influence on it, but together with it co-creates the reality. This article presents the results of the first stage of a survey conducted by the author among consumers of generation Y and Z. The research was carried out within the framework of a research project entitled "Corporate Social Responsibility in the 21st Century". The research was carried out as part of a research project entitled "Corporate Social Responsibility in the XXI Century", as part of statutory research. The research was aimed at confirming the validity of the undertaken research problem and presenting the preliminary results. Obtained results create a possibility to use them to develop marketing strategies, and within their framework to create and implement marketing activities that build long-term relationships with consumers of generations Y and Z, which will contribute to the increase of the effectiveness of the undertaken activities. The article has a research character.
Keywords: consumer; generation Y; generation Z; millenials; corporate social responsibility (CSR).